Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 14: Partial Derivatives - Practice Exercises - Page 864: 14



Work Step by Step

Consider $l=\lim\limits_{(x,y,z) \to (1,-1,-1)} \tan^{-1} (x+y+z)$ and $l=\tan^{-1} (1-1-1)=\tan^{-1} (-1)$ Hence, $l=-\tan^{-1} (\tan (\dfrac{\pi}{4}))=-(\dfrac{\pi}{4})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.